Individual optimisation of swimming start - Prétot, C.; Brunel, T.; Bolon, B.; Clanet, C.; Carmigniani, R. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Unlike most race sports (athletics, kayaking, rowing, track cycling) where the start consists of accelerating as quickly as possible, the swimming start aims to maintain the speed acquired following the push on the pad. Indeed, take-off speeds are of the order of 4.5 m/s (Takeda et al., 2012) when swimming speeds do not exceed 2.1-2.2 m/s. The swimmer therefore reaches his maximum speed in less than a second, which is not the case in other race sports. The first 15 meters of a swim race are called the start phase. The choice of this distance is dictated by the FINA rules (article SW5.3) "from that moment the head must have cut off the surface of the water". For the same reasons we will consider the position of the head passing the 15 meters as the end of this phase of the race. Figure 1 shows a typical trajectory during this race phase. One can cut the trajectory into different parts, corresponding to different movements: the block phase, the flight phase (or more precisely free fall), the glide phase, the undulation phase and finally the swimming phase. This naturally defines the associated transitions: take-off, water entry, activation of undulation, and swim recovery (Vantorre et al., 2014). These phase transitions are very important since they are technically demanding, requiring the right timing. In this paper, we present a model to optimize the swimming start trajectory. We describe the model and tests to evaluate the major parameters. An optimization is done to evaluate the optimal activation velocity and the optimal trajectory.